The role of small specimen creep testing within a life assessment framework for high temperature power plant - Morris, A.; Cacciapuoti, B.; Sun, Wei (Taylor and Francis, 2017)
The safe operation of components operating at high temperature and pressure faces numerous challenges associated with ageing materials and maintaining commercial viability whilst economies transition to a lower carbon future as part of their climate change commitments. Due to these challenges the plant operator faces increasing pressure to ensure that any capital or operational expenditures are optimised and must ensure that they duly recognise plant age, condition, operating regime and ultimately the planned closure date. This review, for the first time, describes how small specimen creep testing can be applied within a practical and deployable life assessment framework and in conjunction with other assessment techniques. The current state of the art for small specimen creep testing is critically reviewed; this also includes a review of traditional techniques used on site for the metallurgical assessment of material condition, with examples from site investigations and assessment campaigns in both conventional and nuclear plant applications. In order to enhance the current practice for assessing the condition of creep ageing components this review proposes the more proactive use of small specimen testing methods for the in-service condition assessment of power plant materials, notably earlier in the plant lifecycle and within a holistic life assessment framework. This is intended to provide a means of calibrating the time dependent response of the component or system being monitored, thereby providing a key reference in-service strain rate measurement, or material property evaluation, that can subsequently be used with other traditionally deployed assessment methods to define a more targeted and cost-effective forward inspection plan. The review describes how small specimen creep testing methods and other complementary tools can be use in a new and structured approach to life management. The current status of small specimen testing methods, for both conventional and nuclear applications, is described along with a detailed discussion on current practice for in-service creep life assessment, with a case study used to illustrate the main principals. A case study is presented for ageing CMV (0.5%Cr0.5%Mo0.25%V) main steam pipework due to the extensive amount of through life data available, which highlights the particular challenges associated with the interpretation of various types of site outage inspection data, in conjunction with on-load plant operational data. The current approach to the assessment of component condition follows well established inspection based practices defined in various industry good practice guides, with expert elicitation and experience used to judge the condition of the component, system and operational risk on return to service. This review proposes a new approach to the holistic life assessment of high temperature plant, with a particular emphasis on more proactive use of small specimen testing. In addition, the review has highlighted other aspects of the current approach to in-service condition assessment that could be improved to support the plant owner. This specifically refers to the potential to develop and implement novel life assessment models that can take advantage of the significant amount of site data currently routinely acquired during plant outage overhauls. There is a clear need to provide the plant owner with more reliable and effective life prediction tools, based on earlier and more rigorous assessment of life consumption. The proposed application of small specimen testing described in this paper is equally applicable to both conventional and nuclear plant applications and a range of components, from static pressure systems to high temperature turbine rotors.